Pendampingan Kepatuhan Pajak Berbasis Digital untuk UMKM di Desa Jlamprang, Kecamatan Wonosobo, Kabupaten Wonosobo - GHONIMAH ZUMROATUN AINIYAH (Fokus ABDIMAS, 2026)
The Community Service Program, themed "Digital-Based MSME Tax ComplianceAssistance," was implemented to improve tax understanding and compliance among Micro,Small, and Medium Enterprises (MSMEs) through the use of digital technology. Low taxliteracy and limited ability to use digital tax services are the main challenges faced by mostMSMEs. This program was conducted through outreach, training, hands-on practice, andmentoring in the use of digital tax services such as e-billing and e-filing. Participants wereMSMEs in the community service partner areas. The results showed an increase inparticipants' understanding of tax obligations and their ability to use digital tax systems.FOKUS ABDIMASJurnal Pengabdian MasyarakatWebsite: ejournal.stiepena.ac.id/index.php/abdimasParticipants began to understand tax reporting procedures, billing code creation, and moreorderly and efficient tax administration. This mentoring program had a positive impact onincreasing MSME tax awareness while supporting the government's digital tax transformationprogram. Therefore, similar activities need to be carried out continuously to further improveMSME tax compliance..Keywords: MSMEs, Tax Compliance, Digitalization, e-Filing, Community Service